A realização do exame de mamografia em mulheres de idades preconizadas residentes no município de Praia Grande, São Paulo - Almeida, Katucha Rocha de (2015)
Introduction: Breast cancer is the most common type of cancer among women, in both developing and developed countries, represented by 25% of all types of diagnosed cancer. Mammography screening for breast cancer is a public health strategy in situations with high incidence numbers and mortality from cancer, as observed in Brazil. Objective: To analyze the performance of mammography screening in Praia Grande city female residents. Methods: A public survey in Praia Grande city, in the state of São Paulo. For the study on undergoing mammography screening exam among 50- to 69 year-old women, according to mammographic screening recommendations, a subsample of 257 women was used, with a non response rate of 0%. Results: Among the 50 to 69 female age-group (257), 70 (27%) underwent mammography screening in the 12 months prior to the survey, more than half (60%) used the public sector service. In the multivariate analysis, breast ultrasound was positively associated with mammography in the last 12 months. Conclusion: Women with recommended ages for tracking the Grand Beach County have low achievement of mammography. The awareness through implementation of public policies on the importance of this examination within what is recommended, to reduce the mortality from the disease, which is a leading cause of death among women in Brazil and worldwide.